Multiple biological characteristics and functions of intestinal biofilm extracellular polymers: friend or foe? - Gong, Fengrong; Xin, Shuzi; Liu, Xiaohui; He, Chengwei; Yu, Xinyi; Pan, Luming; Zhang, Sitian; Gao, Han; Xu, Jingdong (Frontiers in Microbiology, 2024)
The gut microbiota is vital to human health, and their biofilms significantly impact intestinal immunity and the maintenance of microbial balance. Certain pathogens, however, can employ biofilms to elude identification by the immune system and medical therapy, resulting in intestinal diseases. The biofilm is formed by extracellular polymorphic substances (EPS), which shield microbial pathogens from the host immune system and enhance its antimicrobial resistance. Therefore, investigating the impact of extracellular polysaccharides released by pathogens that form biofilms on virulence and defence mechanisms is crucial. In this review, we provide a comprehensive overview of current pathogenic biofilm research, deal with the role of extracellular polymers in the formation and maintenance of pathogenic biofilm, and elaborate different prevention and treatment strategies to provide an innovative approach to the treatment of intestinal pathogen-based diseases.